In situ absorption of molybdate and vanadate during precipitation of hydrotalcite from sodium aluminate solutions - Smith, H.; Parkinson, Gordon; Hart, Robert (Elsevier Science BV, 2005)
Reaction with seawater to produce the layered double hydroxide hydrotalcite is an important means for amelioration of Bayer process wastewater prior to its disposal into the marine environment. This reaction has been synthesised under controlled conditions to elucidate the principal mechanisms involved, particularly those related to absorption of transition metals that are removed from solution.Magnesium?aluminium layered double hydroxides precipitated from reaction between magnesium chloride and synthetic sodium aluminate solution in the presence of transition metal oxyanions have been prepared and characterised using thermal, X-ray and microscopic techniques. The layered double hydroxide precipitated at pH 413 is found to consist of nano-sized hexagonal crystals of final magnesium-aluminium ratio of 2:1, while that precipitated at pHo9.5 has a less well defined crystal structure and final ratio of 4:1. In situ absorption of transition metals from solution into hydrotalcite during precipitation is a pH dependent process. Transition metals are found to replace carbonate in the interlayer space but have little or no overall effect on crystal size or structure. Interlayer distance remains constant in the presence of transition metals, suggesting that these species are intercalated as simple monomeric or dimeric oxyanions, rather than larger polymeric forms.